2006
DOI: 10.1002/adsc.200606045
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Selective Rhodium‐Catalyzed Hydrophosphorylation of Dienes

Abstract: Abstract:The hydrophosphorylation of a model 1,6-diene having a terminal and an internal alkene function has been investigated. Free radical protocols lead invariably to mixtures of cyclic phosphonate products, due to rapid cyclization of the intermediary radical species. Rhodium catalysis using a cyclic pinacol-derived phosphonate provides an efficient technique for the highly selective (> 99 %) hydrophosphorylation at the terminal alkene function. In situ modification of Wilkinsons complex by addition of 2-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…A preliminary control experiment performed with 1,4-cis-homopolyisoprene (using 2.5 mol% of Rh vs. internal C=C bonds) ( Table 2, entry 1) confirmed that (i) no hydrophosphorylation takes place on the poly- Following the conditions optimized for the hydrophosphorylation of the model molecular substrate, [9] initial experiments with PA C H T U N G T R E N N U N G (IP-co-OT) copolymers were conducted using 1,4-dioxane as the solvent (Table 2, entries 2 and 3). However, moderate conversions of the vinyl functions were observed in these conditions, even in the presence of an excess of 2, a phenomenon which is assumed to arise from the poor solubility of the copolymers in this solvent at 100 8C.…”
Section: Catalytic Hydrophosphorylation Of Pa C H T U N G T R E N N Umentioning
confidence: 53%
See 2 more Smart Citations
“…A preliminary control experiment performed with 1,4-cis-homopolyisoprene (using 2.5 mol% of Rh vs. internal C=C bonds) ( Table 2, entry 1) confirmed that (i) no hydrophosphorylation takes place on the poly- Following the conditions optimized for the hydrophosphorylation of the model molecular substrate, [9] initial experiments with PA C H T U N G T R E N N U N G (IP-co-OT) copolymers were conducted using 1,4-dioxane as the solvent (Table 2, entries 2 and 3). However, moderate conversions of the vinyl functions were observed in these conditions, even in the presence of an excess of 2, a phenomenon which is assumed to arise from the poor solubility of the copolymers in this solvent at 100 8C.…”
Section: Catalytic Hydrophosphorylation Of Pa C H T U N G T R E N N Umentioning
confidence: 53%
“…[9] In fact, the linear (anti-Markovnikov) hydrophosphorylation product of the vinyl bond was the only product observed under these conditions; i.e., the catalyst system operates via steric discrimination between internal (substituted) and terminal olefins. This result suggested us that internal C=C bonds such as those present in polyisoprene/polyoctatriene backbones should not be affected.…”
Section: Catalytic Hydrophosphorylation Of Pa C H T U N G T R E N N Umentioning
confidence: 97%
See 1 more Smart Citation
“…The observed A Rh catalyst mediated anti-Markovnikov hydrophosphonylation of alkenes in a polymer to give a linear product (Scheme 16). A catalyst formed from Wilkinson's complex and four equiv of dpph was the most active; this ligand was suggested to be bidentate, but the active Rh species was not identified [26,27].…”
Section: Alkenesmentioning
confidence: 95%
“…No publication has appeared to disclose addition reactions of a phosphine oxide except for cyclopropenes (vide infra). The rhodium-catalyzed addition of pinacol phosphonate has been revisited, focusing on the effect of the ligands using nonconjugated terminal-internal dienes [52]. Only the terminal double bond participates in the reaction to furnish linear products.…”
Section: 'mentioning
confidence: 99%